2010
DOI: 10.3109/9781841847191.001
|View full text |Cite
|
Sign up to set email alerts
|

Definition and epidemiology of stillbirths

Abstract: Stillbirths constitute over half the global perinatal mortality, but only a minority will be registered in any health information system.(1) According to the World Health Organization (WHO) estimates, 3 million stillbirths occurred in 2004 (2), apparently down from 3.3 million in 2000 (1) and 4.3 million in 1995.(3) There is little reason to believe that this trend reflects a decade of success in stillbirth prevention, and the authors of the WHO estimates acknowledge that the latest figures by all accounts are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(78 reference statements)
1
0
0
Order By: Relevance
“…2326 The proportion of stillbirths from chromosomal abnormalities also was similar to other studies. 23,27 A higher proportion of cases in our study were associated with obstetric abnormalities than previously reported in other studies.…”
Section: Commentsupporting
confidence: 89%
“…2326 The proportion of stillbirths from chromosomal abnormalities also was similar to other studies. 23,27 A higher proportion of cases in our study were associated with obstetric abnormalities than previously reported in other studies.…”
Section: Commentsupporting
confidence: 89%